The Phenetic Relationship of Ferns (Polypodiaceae) at the Ascent of Cemoro Kandang, Mount Lawu - Advend Sri Rizky Sianturi (Universitas Negeri Surabaya, 2020)
The fern is one of the highly diverse vascular plant species, which has a unique characteristic. The closely related at the family level because the genera within each family have some uniformity so that the relationship and groupings cannot be distinguished. One example of a diverse fern family is Polypodiaceae. Consequently, it is necessary to simplify the classification; one of them is through phenetic relationship analysis. This study aimed to analyze the phenetic relationship of the Polypodiaceae ferns in Climbing Cemoro, Mouth Lawu enclosure, Karangayar Regency, based on the similarity index on the dendogram. The data were collected using the exploration method and the sporophyte morphological characters were observed. The observations obtained 13 variations of characters. The relationship analysis was carried out with the hierarchical cluster program using SPSS 23. There were six species found from the Polypodiaceae family, there were including Belvisia mucronata, Goniophlebium sp, Lepisorus sp, Pyrrosia piloselloides, Crypsinus taeniatus and Drynaria sparsisora. The finding suggests that six species are divided into two clusters, the Group I consisting of Goniophlebium sp, Lepisorus sp, Lepisorus sp, and Pyrrosia pilloselloides with a similarity coefficient index of 53% and Group II consisting of Drynaria sparsisora, Goniophlebium sp, and Pyrrosia piloselloides with a similarity index of 46%.